Analisis Penggunaan Sistem Informasi Manajemen Pada E-Commerce Shopee - Lusiana Wahyu Eka Agustina (Program Pascasarjana (S2-Ilmu Manajemen) Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
This study aims to analyze the e-commerce management information system on e-ccomerce Shopee to increase online sales and purchases. Knowing the use of management information systems at shopee. Collect data and analyze all available information. The research method used is a qualitative method with a literature study. The data source used is secondary data in the form of various references and previous research on the use of e-commerce. Shopee is present as an online shopping platform in various regions and provides an easy, safe and fast online shopping experience for customers. With the support of various payment methods and various logistics options. Shopee By utilizing the various features available in shopee as well as good management information system controls, online buying and selling activities run more easily and loyal users of e-commerce are increasing.